So They Didn’t Say Yes: How A Scholarship Rejection Taught Me to Work Smarter - Schriefer, Natalie (Author, 2022)
Three years ago, I graduated from my MFA program. I wanted to hit the ground running, so right from the start, I crafted myself a ritual: around the first of each month, I’d spend a morning scouring listservs and social media for writing opportunities. I tracked submissions calls, literary magazine
Keywords: dept.hhs